Pengaruh Proses Rekrutmen, Seleksi dan Pelatihan Kerja Terhadap Peningkatan Kinerja Karyawan pada PT. RTKCM (Rahmat Tunas Karya Citra Mandiri) Padang Sidempuan - Laila Safitri Nasution; Sarah Imelda; Pitono (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
This study aims to determine the effect of the recruitment process on improving employee performance, to determine the effect of selection on improving employee performance and to determine the effect of job training on improving employee performance. The population in this study were human resources employees at PT. RTKCM (Rahmat Tunas Karya Citra Mandiri) Padangsidempuan, amounting to 115 people, and the sample used is 115 respondents using saturated sampling. The analysis technique used is multiple linear regression.The results showed that the recruitment process variable had a positive and significant effect on improving employee performance at PT. RTKCM (Rahmat Tunas Karya Citra Mandiri) Padangsidempuan. The selection variable has a positive and significant effect on improving employee performance at PT. RTKCM (Rahmat Tunas Karya Citra Mandiri) Padangsidempuan. And the job training variable has a positive and significant effect on improving employee performance at PT. RTKCM (Rahmat Tunas Karya Citra Mandiri) Padangsidempuan. Ways that can be done to improve employee performance include improving the recruitment, selection and job training processes for employees of PT. RTKCM (Rahmat Tunas Karya Citra Mandiri) Padangsidempuan, which is indicated by the coefficient of determinasi (R2) of 0,498. The employees can have better performance skills and are motivated to perform well on the job and in other training programs.